Pengaruh Kompetensi, Independensi, Integritas, Akuntabilitas dan Profesionalisme terhadap Kualitas Audit di Pemerintahan Daerah (Studi Empiris Pada Inspektorat Provinsi Jambi) - Rika Neldawati; Asrini Asrini; Suherman Suherman; Muhammad Amali (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of competence, independence, integrity, accountability and professionalism on audit quality in local government at the inspectorate of Jambi Province. Several previous studies regarding audit quality show different results. Therefore, other research needs to be done to retest the theory about audit quality. The independent variables in this study are Competence, Independence, Integrity, Accountability and Professionalism. For the dependent variable in this study is audit quality. This research was conducted at the Inspectorate Office of Jambi Province. The data in this study were primary data obtained from distributing questionnaires directly to the Inspectorate Office of Jambi Province. The results of this study partially show that the characteristics of independence and integrity, while competence, accountability, professionalism have no effect on audit quality. The results of this study simultaneously influence audit quality